Case Report: Clinical and Hematological Characteristics of εγδβ Thalassemia in an Italian Patient - Fotzi, Ilaria; Pegoraro, Francesco; Chiocca, Elena; Casini, Tommaso; Mogni, Massimo; Veltroni, Marinella; Favre, Claudio (Frontiers in Pediatrics, 2022)
Introduction εγδβ thalassemia is a rare form of β-thalassemia mostly described in children originating from Northern Europe. Only anecdotic cases from the Mediterranean area are reported. The diagnosis is challenging, considering the rarity of the disease and its heterogeneous clinical presentation. Most patients have neonatal microcytic anemia, sometimes requiring in utero and/or neonatal transfusions, and typically improving with age. Case Description We report on an Italian newborn presenting with severe neonatal anemia that required red blood cell transfusion. After the first months of life, hemoglobin levels improved with residual very low mean corpuscular volume. β and α thalassemia, IRIDA syndrome, and sideroblastic anemia were excluded. Finally, a diagnosis of εγδβ thalassemia was made after microarray analysis of single nucleotide polymorphisms revealed a 26 kb single copy loss of chromosome 11p15.4, including the HBD, HBBP1, HBG1, and HBB genes. Conclusions Despite its rarity, the diagnosis of εγδβ thalassemia should be considered in newborns with severe neonatal anemia requiring in utero and/or neonatal transfusions, but also in older infants with microcytic anemia, after excluding more prevalent red blood cell disorders.